Clinical Profile and Colonoscopic Findings in Patients with Ulcerative Colitis at a Tertiary Care Hospital in Nepal: a Cross Sectional Study
Background and aims: Ulcerative Colitis (UC) is an inflammator condition confined to the colon. Ulcerative colitis commonly presents with rectal bleeding, bloody diarrhea and abdominal pain. This research was undertaken to study the clinical profile and colonoscopic findings of the patient presenting with ulcerative colitis in a tertiary care center at Gandaki Province, Nepal . Methods: A hospital based prospective observational study was conducted from November 2017 till June 2020 in department of Medicine at Manipal teaching Hospital, Pokhara, Nepal after obtaining ethical approval from Institutional Research Committee and informed consent from patients or their relatives. Clinical profile and colonoscopic findings of patients with Ulcerative colitis were studied. Results: Results: Out of 274 colonoscopies, 60 patients (M:F= 3: 2) were diagnosed with UC. The mean age of subjects was 37